Some Afforestation Problems and Research Needs in Relation to Erosion Control in Arid and Semi-arid Parts of Rajasthan - Bhimaya, C. P.; Kaul, R. N. (Indian Forester, 1960)
The western portion of Rajasthan is all desert. The area of this desert is over 70,000 sq. miles. Wind is attributed to be the main agency responsible for the creation and continuance of this desert. Extremes of temperature, high wind velocity, scanty rainfall and low relative humidity are the main climatic features of this desert. Inspite of these factors, Rajasthan desert has a variety of natural vegetation, which is fast disappearing due to continued uncontrolled grazing and felling of trees, resulting in excessive wind erosion and desert extension. In fact, there is evidence to show that during past geological times this desert region was covered with dense vegetation. Large lignite deposits are discovered at Palana in Bikaner district which is now the heart of the desert. Thus, there is a possibility of averting this catastrophe by conserving the existing vegetation and rehabilitating the landscape with vegetation. Indigenous flora can be utilised easily for afforesting these areas and checking wind erosion. Technique of rehabilitating the various soil types met with in the desert region are under study at the Desert Afforestation and Soil Conservation Station at Jodhpur and the information so far collected is presented here. The low and extremely variable rainfall is one of the most serious limiting factors in the way of restoring vegetative cover on denuded, arid and semi-arid lands. Intensive studies of climate and micro-climate are necessary to understand and effectively control the adverse climatic factors. The selection of suitable species and superior strains from amongst indigenous as well as exotic xerophytic flora and the development of suitable arid-land afforestation techniques including nutritional requirements for various species are other important lines of investigation. The stabilisation of sand dunes and establishment of protective windbreaks and shelter belts are essential to check sand drift and advancing aridity from the desert areas. Research is also required on the most economical use of water for arid afforestation and on problems connected with inducement of drought-resistant character in the seed, the use. Of foliar sprays on plants to bring about drought resistance, and suitable methods of "hardening" of plants prior to planting out.